2021
DOI: 10.3389/fonc.2021.768264
|View full text |Cite
|
Sign up to set email alerts
|

SOX9: Advances in Gynecological Malignancies

Abstract: Transcription factors of the SOX family were first discovered in mammals in 1990. The sex-determining region Y box 9 belongs to the SOX transcription factor family. It plays an important role in inducing tissue and cell morphogenesis, survival, and many developmental processes. Furthermore, it has been shown to be an oncogene in many tumors. Gynecological malignancies are tumors that occur in the female reproductive system and seriously threaten the lives of patients. Common gynecological malignancies include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 91 publications
(116 reference statements)
0
4
0
Order By: Relevance
“…Our study not only highlights DYRK3 as a tumor-promoting oncogene in SOC but also elucidates its potential as a therapeutic target by demonstrating the inhibitory effects of DYRK3 knockdown on cell viability, invasion, and in vivo tumor growth. By analyzing the correlation between DYRK3 and EMT-related genes [ 8 ] in TCGA-ovarian cancer dataset, we observed a positive correlation between DYRK3 with FLNB and SOX9, both of which had been well acknowledged as oncogenic molecules in tumorigenesis and cancer progression [ 10 13 ]. We also found that knockdown of DYRK3 can downregulate the protein expression of filamin B and SOX9.…”
Section: Discussionmentioning
confidence: 99%
“…Our study not only highlights DYRK3 as a tumor-promoting oncogene in SOC but also elucidates its potential as a therapeutic target by demonstrating the inhibitory effects of DYRK3 knockdown on cell viability, invasion, and in vivo tumor growth. By analyzing the correlation between DYRK3 and EMT-related genes [ 8 ] in TCGA-ovarian cancer dataset, we observed a positive correlation between DYRK3 with FLNB and SOX9, both of which had been well acknowledged as oncogenic molecules in tumorigenesis and cancer progression [ 10 13 ]. We also found that knockdown of DYRK3 can downregulate the protein expression of filamin B and SOX9.…”
Section: Discussionmentioning
confidence: 99%
“…In endometrial cancer, upregulation of SOX9 could promote endometrial cell proliferation, induce endometrial precancerous lesions, and predict the prognosis of endometrial cancer patients in combination with the expression of other genes. In uterine sarcoma, upregulation of SOX9 promotes epithelial-mesenchymal transition, leading to sarcoma formation ( Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…SOX9 also plays an important role in other types of gynecological malignancies. In ovarian epithelial tumors, many studies have found that SOX9 is significantly higher in tumor tissue than in normal ovarian tissue, and its expression correlates with overall survival and progressionfree survival of ovarian cancer patients; elevated expression of some miRNAs can suppress SOX9 expression, thereby Frontiers in Genetics frontiersin.org inhibiting ovarian cancer cell growth and multicellular spheroids formation; ceRNA network-regulated SOX9 expression is involved in the development of ovarian cancer, maintenance of tumor stem cell properties, antiapoptosis, migration, and invasion; meanwhile, SOX9 expression is associated with chemoresistance resistance in ovarian cancer patients (Chen et al, 2021). Recent studies have also demonstrated that cytoplasmic SOX9-mediated cell death inhibition contributes to the survival of cancer stem cells in high-grade ovarian cancer (Oh et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…Up to now, the obscurity of the molecular mechanisms related to the incidence and development of gynecological malignancies has been the main theme of the studies. Recent studies have reported that multiple mechanisms play a role in the regulation of the expression of the sex-determining region Y-box 9, which leads to the emergence and development of gynecological malignancies 10 . In addition, members of the SOX family contain a conserved high mobility group DNA binding domain.…”
Section: Introductionmentioning
confidence: 99%